2015
DOI: 10.1080/21645515.2015.1074361
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of early vs delayed BCG vaccination in moderately preterm (31–33 weeks) infants

Abstract: Minimum gestation at which infant can be given BCG (Bacillus Calmette-Guerin) vaccine safely at birth is not clearly defined. Our objectives were the following: to compare Mantoux test after 6 months of BCG immunization in moderately preterm babies (31-33 weeks) vaccinated at birth and 34 weeks post conception age and to compare in above groups:(a) Interferon -gamma (IFN-g) levels in BCG vaccinated infants who did not react to Mantoux test (b) Local BCG reaction at 6, 10, 14 weeks and 6 months (c) Complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
0
28
1
3
Order By: Relevance
“…Furthermore, of importance to global health, these findings support the hypothesis, that in the appropriate context in countries in which neonatal immunization with BCG is recommended, concurrent administration of (BCG + HBV) at birth to the moderate to late preterm and term newborn may enhance the protective response to HBV immunization. Of note, in relatively small preterm studies thus far, BCG has been immunogenic and safe when administered to the moderately to late preterm infant [31–33 weeks GA] ( 80 ). Further studies of the safety, efficacy and mechanism of action of the combination of (BCG + HBV) compared to each alone in newborn animals, including humans, will shed further light into this important area crucial to the protection of the most vulnerable among us.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, of importance to global health, these findings support the hypothesis, that in the appropriate context in countries in which neonatal immunization with BCG is recommended, concurrent administration of (BCG + HBV) at birth to the moderate to late preterm and term newborn may enhance the protective response to HBV immunization. Of note, in relatively small preterm studies thus far, BCG has been immunogenic and safe when administered to the moderately to late preterm infant [31–33 weeks GA] ( 80 ). Further studies of the safety, efficacy and mechanism of action of the combination of (BCG + HBV) compared to each alone in newborn animals, including humans, will shed further light into this important area crucial to the protection of the most vulnerable among us.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 14 , 20 , 21 , 22 , 23 , 31 , 32 reported scar formation and TST conversion and were therefore included in a meta-analysis. Only data on infants who were preterm and/or LBW and had follow-up adequate to record scar formation (n = 515) or TST conversion (n = 397) were included.…”
Section: Resultsmentioning
confidence: 99%
“… 62 A trial in India on 180 neonates born between 31 to 33 weeks’ gestational age reported 2 infants in each of the early and late vaccination groups with nonsuppurative lymphadenopathy (a total of 4 individuals). 21 There were no other adverse reactions, and meta-analysis was not possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from other studies suggest also that the preterm infants born at 32-36 weeks of gestation can be effectively immunized with BCG at birth. 199,200,201,202 In a Brazilian study a typical BCG scar was verified in 96.9% of the control group and in 90.0% of the preterm infants. 203 In contrast a study which evaluated the efficacy of BCG vaccine in pre-term infants in UAE concluded that male pre-term infants of lower gestational ages (<33 weeks) are less likely to develop BCG scar and a reactive PPD tuberculin test after BCG vaccination.…”
Section: Vaccination Of Low Birth Weight and Premature Infantsmentioning
confidence: 93%